2019
DOI: 10.1038/s41419-019-1890-9
|View full text |Cite
|
Sign up to set email alerts
|

High throughput circRNA sequencing analysis reveals novel insights into the mechanism of nitidine chloride against hepatocellular carcinoma

Abstract: Nitidine chloride (NC) has been demonstrated to have an anticancer effect in hepatocellular carcinoma (HCC). However, the mechanism of action of NC against HCC remains largely unclear. In this study, three pairs of NC-treated and NC-untreated HCC xenograft tumour tissues were collected for circRNA sequencing analysis. In total, 297 circRNAs were differently expressed between the two groups, with 188 upregulated and 109 downregulated, among which hsa_circ_0088364 and hsa_circ_0090049 were validated by real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 37 publications
3
41
0
Order By: Relevance
“…As demonstrated previously, a decreased MAOA was detected in HCC patients and correlated with poor prognosis. Our previous studies have confirmed the anti‐HCC effect of NC 34,35,37 . In this study, in vivo experiment showed that the tumor volumes were reduced and the MAOA expression level was significantly elevated in the NC‐treated group compared with the control group.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As demonstrated previously, a decreased MAOA was detected in HCC patients and correlated with poor prognosis. Our previous studies have confirmed the anti‐HCC effect of NC 34,35,37 . In this study, in vivo experiment showed that the tumor volumes were reduced and the MAOA expression level was significantly elevated in the NC‐treated group compared with the control group.…”
Section: Discussionsupporting
confidence: 77%
“…Our team has been studying the biological function NC has on HCC for a period. Previous in vitro and in vivo studies have verified that TCM NC exhibits a strong anti‐HCC capability by mediating complicated mechanisms, namely TF‐miRNA‐mRNA axis, circRNA‐miRNA‐mRNA network, andJAK1/STAT3 cascade signaling inhibition 34‐38 . Given the role that MAOA plays in HCC, we supposed that NC could exert its anti‐tumor effect partially by influencing the expression of MAOA .…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…As a newly emerging member of the non-coding RNA family, circRNAs have gained extensive attention recently, owing to the advances in bioinformatics approaches and widespread use of transcriptome sequencing (22,23). Accumulating research has suggested that circRNAs are involved in a variety of disease processes owing to their unique characteristics, such as high abundance, structural stability, and conservation across species (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The research on circRNAs is still in his infancy and their specific functions in several physiological processes and in the pathogenesis of human diseases is still largely unknown. However, recently high-throughput sequencing studies on clinical tumor samples showed a deregulation of circRNAs expression in tumors 138,139 . In particular, their downregulation has been described in proliferative cells across different tumor types, indicating that some circRNAs may have tumor suppressive roles.…”
Section: Circular Rnasmentioning
confidence: 99%